Le unioni civili fra Giudice e Legislatore (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La posizione del giudice ordinario. – 2. Le decisioni della Corte costituzionale. – 3. Il "pregresso vissuto" e le sollecitazioni al legislatore del giudice costituzionale e della Corte di Cassazione. – 4. L'intervento del legislatore "messo in mora".The civil unions between judicial and legislative powerThe essay traces the stages of the dialogue between judges and legislator that led to the approval of the law n. 76/2016. In particular, the essay emphasizes the relevance of the role of the ordinary judges who, understanding the importance of the right to a steady union for homosexual couples, have then appointed the Constitutional Court to solve this delicate problem. With two decisive rulings, the Court has laid out the way for the intervention of the legislator.